2006
DOI: 10.1142/s0217751x06035087
|View full text |Cite
|
Sign up to set email alerts
|

Black Hole Cross-Section at the LHC

Abstract: Black hole production at the Large Hadron Collider (LHC) was first discussed in 1999. Since then, much work has been performed in predicting the black hole cross section. In light of the start up of the LHC, it is now timely to review the state of these calculations. We review the uncertainties in estimating the black hole cross section in higher dimensions. One would like to make this estimate as precise as possible since the predicted values, or lower limits, obtain for the fundamental Planck scale and numbe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 63 publications
(94 reference statements)
0
18
0
Order By: Relevance
“…This approximation can be modified by a number of effects depending on mass, angular momentum, electric charge, colour, and finite size of the incoming particles. The current results, though far from complete, indicate that the simple geometric cross section is correct if multiplied by a formation factor of order unity [17]. A striking feature of the black disc cross section is its rise with the centre-of-mass energy which distinguishes black hole production from any perturbative process.…”
Section: Black Hole Production and Decaymentioning
confidence: 60%
“…This approximation can be modified by a number of effects depending on mass, angular momentum, electric charge, colour, and finite size of the incoming particles. The current results, though far from complete, indicate that the simple geometric cross section is correct if multiplied by a formation factor of order unity [17]. A striking feature of the black disc cross section is its rise with the centre-of-mass energy which distinguishes black hole production from any perturbative process.…”
Section: Black Hole Production and Decaymentioning
confidence: 60%
“…For example, initial-state beam radiation or radiation during a balding phase could reduce the cross section by several orders of magnitude (see Ref. [25] for a review of the ADD case).…”
Section: Production Cross Sectionmentioning
confidence: 99%
“…The effects of finite size have been examined [12,13] and only recently have angular momentum [14] or charge been discussed [15]. Although these results are far from complete, they do indicated that the simple geometric cross section is correct if multiplied by a formation factor of order unity [16].…”
Section: Introductionmentioning
confidence: 99%